PEMODELAN 3D ANALYSIS RISIKO BENCANA WISATA LERENG GUNUNG MERAPI DI KECAMATAN CANGKRINGAN DAN PAKEM - Rahma Nur Hasanah; Riko Arrasyid; Ridho Dwi Sumanto; Yoga Munawar Khahfi (Jurnal Samudra Geografi, 2023)
As a country located in an area where three active plates meet, Indonesia has a high level of disaster risk, including volcanic eruptions. Indonesia has active volcanoes more than 30% of all active volcanoes in the world. One of the most frequent volcanoes that erupts is Mount Merapi, since 1900 up to now there have been recorded 24 eruptions. From our concern about the threat of disaster, we are interested in developing 3D Analysis modeling for tourist areas in Cangkringan and Pakem Districts. The combination of GIS technology with navigation systems can be used as a tool to analyze the state of tourist areas against disasters from Mount Merapi. From the 3D Analysis modeling that has been made, Bukit Klangon which is opened to the public is the highest position compared to other tourist sites and has the closest distance to the caldera. However, in spatial calculations, this tourism location is not one of the tourist areas with the highest hazard vulnerabilities.